KAJIAN INTRAESTETIK DAN EKSTRAESTETIK MUSIK SENGGAYONG DI DESA PANGKALAN BUTON KECAMATAN SUKADANA KABUPATEN KAYONG UTARA - Irawan, Purna Aji; Ghozali, Imam; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This research was motivated by the unique sound and function of Senggayong music. The method used in this research is qualitative method. Sources of data in this study was Senggayong conservationists, who understand the ins and outs of Senggayong. The main data collection tool in this study is the researcher himself as a key instrument. Based on the results of an intraesthetic study, the Senggayong musical instrument consists of three pairs, namely Senggayong anak,induk, and kaul. There are two timbre of Senggayong music namely dong and ket. In Senggayong music, there are several titles of Senggayong music that are commonly played, including mogak,anjing nyalak, timang buah, pangkut and hujan deras. Based on studies of extraesthetic research Senggayong music has several functions including as a means of communication, education and entertainment. Senggayong music includes traditional music because it fulfills the characteristics of traditional music such as not having a notation, the players are not specified, are learned verbally, involve more local musical instruments and are part of the culture of the community. This research is expected to provide knowledge about traditional music in North Kayong district so that the community will help preserve it.Keywords: Senggayong Music, Intraesthetic Study, Extraesthetic Study